(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
Probiotics are live microorganisms, good bacteria which when consumed in sufficient quantities will be beneficial for the host. Found in the digestive tract as normal flora, mostly from the Lactobacillus spp group, which is often used in the food industry because of its multiple properties. The product of probiotic milk fermentation technology is already popular in the community, now it is present in the form of various food and beverage preparations. Milk fermented with Lactobacillus acidophilus or its combination with Bifidobacterium sp. known as yogurt is beneficial for health and serves as a healthy food. In the framework of the 59th Anniversary, the Community Service Team of the Faculty of Pharmacy, Airlangga University Surabaya has held training activities for the academic community of STIKES Ibnu Sina Purwokerto as partners with the theme of making processed milk drinks using probiotic fermentation technology based on fresh fruit juice to produce a unique healthy food. In collaboration with the Head of UPTD Pemda Pekuncen Banyumas, technology transfer activities were performed in the form of two days of training consisting of material debriefing, demonstration, training, consultation, and evaluation of training results. Community service activities are also expected to increase the economic value of cow/etawa milk, which includes surplus products in partner areas. It is hoped that the tenant community will be inspired to develop healthy drink products based on the probiotic milk fermentation technology facilitated by the UPTD Pemda Pekuncen Banyumas. — Probiotik adalah mikroorganisme hidup, dikenal sebagai bakteri baik yang apabila dikonsumsi dalam jumlah cukup akan menguntungkan bagi inangnya. Ditemukan dalam saluran pencernaan sebagai flora normal, paling banyak dari kelompok Lactobacillus spp, yang sering digunakan dalam industri makanan karena multi khasiatnya. Produk teknologi fermentasi susu probiotik sudah popular di masyarakat, kini hadir dalam bentuk berbagai sediaan makanan dan minuman. Susu yang difermentasi dengan Lactobacillus acidophilus atau kombinasinya dengan Bifidobacterium sp. dikenal dengan nama yoghurt yang bermanfaat untuk kesehatan dan berfungsi sebagai Makanan Kesehatan. Dalam rangka Dies Natalis yang ke-59, Tim Pengabdian masyarakat Fakultas Farmasi Universitas Airlangga Surabaya telah menggelar kegiatan pelatihan bagi sivitas akademika STIKES Ibnu Sina Purwokerto sebagai mitra dengan tema pembuatan minuman susu olahan menggunakan teknologi fermentasi probiotik berbasis sari buah segar, sehingga menghasilkan minuman khas yang menyehatkan. Bekerjasama dengan Kepala UPTD Pemda Pekuncen Banyumas, kegiatan alih teknologi dilakukan dalam bentuk pelatihan selama dua hari terdiri dari kegiatan pembekalan materi, peragaan, pelatihan, konsultasi dan evaluasi hasil pelatihan. Kegiatan pengabdian kepada masyarakat juga diharapkan dapat meningkatkan nilai ekonomi susu sapi/etawa. yang termasuk produk surplus di daerah mitra. Masyarakat tenan juga diharapkan terinspirasi untuk mengembangkan produk minuman sehat berbasis teknologi fermentasi susu probiotik dengan difasilitasi oleh UPTD Pemda Pekuncen Banyumas.